The use of laser scanning in the survey of the postern of the Kłodzko Fortress - Gleń, Piotr; Krupa, Karol (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2020)
This article presents the significance of laser scanning as a method of acquiring spatial data and the significance of this method during the process of survey of historic monuments. The authors of the paper focus on the survey of the postern located under the eastern slope of the Kłodzko Fortress and connecting the town with the upper levels of the fortification. With the use of laser scanning, a three-dimensional image of the postern was obtained. Based on the results of measurements, it is possible to specify the dimensions of tunnel elements which are difficult to measure, such as the buried fragment of the postern and the height of the embankment located above the tunnel. The research conducted by the authors of the article has been juxtaposed with the available archival materials concerning this part of the Kłodzko Fortress.